Squaric Acid-Containing Hole-Collecting Monolayer Materials for p–i–n Perovskite Solar Cells - Shota Hira (14231739) (2025)
The development of hole-collecting materials is indispensable to improving the performance of perovskite solar cells (PSCs). To date, several anchorable molecules have been reported as effective hole-collecting monolayer (HCM) materials for p–i–n PSCs. However, their structures are limited to well-known electron-donating skeletons, such as carbazole, triarylamine, etc. In this work, we developed a series of squaraine derivatives that have a π-conjugated core composed of a squaric acid moiety connected to an indoline moiety. Thanks to the polar carbonyl group of squaric acid, all of the molecules were found to form hydrophilic monolayers after being chemisorbed on transparent conducting oxide surfaces, which is beneficial for the subsequent deposition of the perovskite layer. The effect of the substituents on the squaric acid moiety and the anchoring groups connected to the indoline moiety on the molecular electronic structure as well as the solar cell device’s performance was elucidated. The p–i–n PSC devices fabricated by using these squaraine derivatives as hole-collecting monolayer materials exhibited high power conversion efficiencies of up to 22.1%, together with good stability. This work highlights the potential of a simple squaric acid skeleton as the building block for hole-collecting monolayer materials to realize high-efficiency and cost-effective PSCs.